(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2022)
The study was conducted to investigate the soil properties and pesticide intensity in rice, banana and brinjal growing agricultural land of Delduar and Sakhipur upazila of Tangail district during July 2019 to June 2020. Forty five soil samples were collected from different crop land at the study area and analyzed in the Soil Resource Development Institute to determine the soil properties as pH, total organic matter (OM), total nitrogen (N), available phosphorus (P), available sulfur (S), available zinc (Zn), exchangeable potassium (K), exchangeable magnesium (Mg) and exchangeable calcium (Ca). However, pesticide used intensity was also evaluated through questionnaire survey with farmers and stakeholders in the study area. Results showed that pH, OM, available N, exchangeable Ca and exchangeable Mg content were significantly higher in rice growing land than banana and brinjal. On the other hand, available P, exchangeable K and available Zn content were substantially higher in brinjal growing land than rice and banana. The OM showed significant positive correlation with soil pH, available N, available S, exchangeable Mg and exchangeable Ca (r=0.37, 0.99, 0.31, 0.59 and 0.63, respectively), indicated rice growing land built up these soil properties through increasing soil OM. The available P showed significant and positive correlation with K and Zn (r=0.55 and 0.74, respectively), but negative correlation with exchangeable Mg and exchangeable Ca (r=-0.53 and -0.32, respectively). The exchangeable K showed significant and positive correlation with available Zn (r=0.45) but negative correlation with exchangeable Mg (r=-0.37). The Mg showed significant negative correlation with available Zn (r=-0.45) but positive correlation with exchangeable Ca (r=0.87). Results also revealed that pesticide used intensity was higher in brinjal followed by banana and minimum in rice crop. Study suggests that farmers require up-to-date information on soil nutrient status so that they may use the proper utilization of fertilizers and avoid using excessive amounts of fertilizers and pesticides in their crop land. Int. J. Agril. Res. Innov. Tech. 11(2): 85-94, Dec 2021